DESCRIPTION OF FAMOUS MUHADDIS IN “KUTUBI SITTAH AND AUTHORS” - Gulnoza Alijonova (Journals Park Publishing, 2022)
The science of hadith has not lost its importance as a sacred source of muslims for centuries. “Kutubi sittah and authors” by Rezauddin ibn Fakhriddin is considered one of the educational literature written for the field of hadith studies of the 20th century. The article describes the authors of “Kutubi sittah” and their scientific activities.
Keywords: Imam Bukhari, Imam Muslim, Imam Nasa'i, hadith studies